Analisis Pengaruh Situasi, Produk, Individu pada Perilaku Membeli dan Mengkonsumsi Makanan Ringan - Rita, Rita; Wandrial, Son; Inderadi, Regina (Bina Nusantara University, 2015)
The study of consumer behavior is expected to receive more academic attention from scholars. The important aspects in consumer behavior are purchasing and consumption behavior by individuals. Purchasing and consumption behavior is influenced by situation, product and person. The objectives of this research are to examine main and interaction effects of consumption situation, snack products, and individual characteristics onpurchasing and consumption behavior. This research was conducted in Jakarta using 218 respondents that has purchased and consumed snack products which were offered by researcher. The situation used in this research is consumption situation based on tasks definition, which the consumer purchases and consumes products based on purpose and objectives of purchases and consumption contetxs. Whereas individual characteristics used is observable characteristics such as age, gender, and level of education. Thus, the result show that individual characteristics based on age will interact with consumption situation and snack products which influence purchasing and consumption behavior. This is a fully model which influence purchasing and consumption behavior. The pattern of variance light /salty/ crispy snack, baby boomer and informal serving situation is thehighest contribution to influence purchasing and consumption behavior.